A Comparative Study of Islamic Philanthropy in the Tafsir al-Jami' li-Ahkam al-Quran and Fi Zilal al-Quran - Ummu Aina Nafidatul Khusnah,; Muhammad Faiz,; Mohammad Yahya, (Advances in Humanities and Contemporary Studies, 2025)
The term philanthropy is a new term in Islam, but the practice has existed for 15 centuries, since the time of the Prophet Muhammad. In Islamic tradition, through the commands of zakat, infaq, sadaqah, and waqf, the understanding of philanthropy is deeply rooted in these practices.  New innovations in the study of the Qur'an have emerged through interpretive activities, resulting in a variety of interpretive works differing in terms of sources, methods, and interpretive styles. Therefore, this study aims to understand how to interpret Islamic philanthropy in the context of classical and modern interpretations by analyzing the similarities and differences in the interpretations of Imam Al - Qurṭubi in the book Tafsir Al-Jâmi’ Li Ahkâm Al-Qur’ân and Sayyid Quṭb in the book Tafsir Fî âilâl Al-Qur’ân. The method used in this study is a qualitative method with library research and descriptive-analytical techniques in analyzing the data. The results of the study show that the similarities in interpretation lie in how Imam Al-Qurṭubi and Sayyid Quṭb explain in their tafsir that: 1) Both interpret zakat as a form of faith that purifies the soul, 2) Infak is understood as a tangible manifestation of faith, because wealth is a trust from Allah that must be spent sincerely in His path. 3) Charity is interpreted as a sincere spiritual investment from a servant, 4) Both emphasize the importance of spending the most beloved wealth sincerely as a condition for achieving perfect virtue. The difference in their interpretations lies in the fact that Imam Al-Qurṭubi emphasizes the legal aspects in interpreting the verses on Islamic philanthropy, while Sayyid Quṭb elaborates on the wisdom, meaning, and social aspects contained within them.